2022
DOI: 10.1021/acs.jmedchem.2c00377
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Transmembrane AMPA Receptor Regulatory Proteins by Positron Emission Tomography

Abstract: The transmembrane α-amino-3-hydroxyl-5-methyl-4-isoxazolepropionic acid (AMPA) receptor regulatory protein γ-8 (TARP γ-8) constitutes an auxiliary subunit of AMPA receptors, which mediates various brain functions including learning and memory. TARP γ-8 has emerged as a promising therapeutic target for central nervous system disorders. Despite considerable efforts, previously reported TARP γ-8 PET radioligands, such as [ 11 C]TARP-1903 and [ 11 C]TARP-1811 series, were plagued by limited brain uptake and/or hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…[ 11 C]TARP-2105 was recently developed as a promising PET ligand for TARP c-8 imaging in our research group. 18 In that report, in vitro autoradiography studies of [ 11 C]TARP-2105 showed heterogeneous radioactive accumulation in the brain in the following rank order: hippocampus, frontal cortex, striatum, thalamus, and cerebellum. The radioactive signals were successfully decreased by administration of the TARP c-8-selective inhibitor JNJ-55511118.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…[ 11 C]TARP-2105 was recently developed as a promising PET ligand for TARP c-8 imaging in our research group. 18 In that report, in vitro autoradiography studies of [ 11 C]TARP-2105 showed heterogeneous radioactive accumulation in the brain in the following rank order: hippocampus, frontal cortex, striatum, thalamus, and cerebellum. The radioactive signals were successfully decreased by administration of the TARP c-8-selective inhibitor JNJ-55511118.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, parametric images (Figure 4(d)) of the BP ND based on the ratio method showed more obvious contrast with a wide range of signal than images obtained using the SRTM. 18 The reference tissue model for PET with [ 11 C]TARP-2105 could be selected according to the research purpose. For example, when a BP ND with R1 information is needed, the SRTM can be used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[15] Through our continuous efforts in this target, an 11 C-labeled radioligand, TARP-2105, was discovered with reasonable brain uptake and specific binding towards TARP γ-8 based on scaffold JNJ-55511118. [16] However, the limited half-life of carbon-11 has constrained the broader clinical translation and utilization. To address this limitation, in this study, we developed two novel 18 F-labeled radioligands, namely [ 18 F]TARP-2204 and [ 18 F]TARP-2205, both derived from TARP-2105 derivatives.…”
Section: Introductionmentioning
confidence: 99%